Autobiographical memory and narrative in childhood - Fivush, Robyn ca. 20./21. Jh (Cambridge elements, 2022)
This Element delineates how the narrative expression of autobiographical memory develops through everyday interactions that frame the forms and functions of autobiographical remembering. Narratives are both outward and inward facing, providing the interface between how we perceive the world and how we perceive ourselves. Thus narratives are the pivot point where self and culture meet. To make this argument, the author brings together literature from multiple perspectives, including cognitive, personality, evolutionary, cultural, and developmental psychology. To fully understand autobiographical memory, it must be understood how it functions in the context of lives lived in complex sociocultural contexts